Selective Estrogen Receptor Modulators: A Potential Option For Non-Binary Gender-Affirming Hormonal Care? - Xu, Jane Y.; O’Connell, Michele A.; Notini, Lauren; Cheung, Ada S.; Zwickl, Sav; Pang, Ken C. (Frontiers in Endocrinology, 2021)
Gender dysphoria describes the distress associated with having a gender identity that differs from one’s birth-assigned sex. To relieve this distress, transgender and gender diverse (henceforth, trans) individuals commonly undergo medical transition involving hormonal treatments. Current hormonal treatment guidelines cater almost exclusively for those who wish to transition from male to female or vice versa. In contrast, there is a dearth of hormonal options for those trans individuals who identify as non-binary and seek an androgynous appearance that is neither overtly male nor female. Though prolonged puberty suppression with gonadotrophin releasing hormone agonists (GnRHa) could in theory be gender-affirming by preventing the development of unwanted secondary sex characteristics, this treatment option would be limited to pre- or peri-pubertal adolescents and likely have harmful effects. Here, we discuss the theoretical use of Selective Estrogen Receptor Modulators (SERMs) for non-binary people assigned male at birth (AMAB) who are seeking an androgynous appearance through partial feminisation without breast growth. Given their unique range of pharmacodynamic effects, SERMs may represent a potential gender-affirming treatment for this population, but there is a lack of knowledge regarding their use and potentially adverse effects in this context.